A batch method for estimating thrombin clottable fibrinogen. Issue 10 (October 1973) - Farrell, G. W.; Wolf, P.
Abstract : A method for estimating thrombin clottable fibrinogen in a large number of plasma samples is described. This method is based on measuring the optical density difference of a diluted plasma and its corresponding serum after incubation at 59°C in the presence of 10% NaCl. The method gave excellent correlation with previously described thrombin clottable estimates, but was easier to perform and more accurate when estimating friable thrombin clots. The method is compared with measurements of heat-coagulable plasma protein described by Thorp (1967) and by Millar, Simpson, and Stalker (1971), and direct optical density measurement of plasma after thrombin treatment (Burmester, Aulton, and Horsfield, 1970). The feasibility of automating the proposed technique together with immunoreactive fibrinogen estimates is discussed.